From childhood to adulthood: health care use in individuals with cerebral palsy. (31st August 2018) - Roquet, Marion; Garlantezec, Ronan; Remy‐Neris, Olivier; Sacaze, Elise; Gallien, Philippe; Ropars, Juliette; Houx, Laetitia; Pons, Christelle; Brochard, Sylvain
Abstract : Aim: To analyse the health care usage of individuals with cerebral palsy (CP) as a function of age and ambulatory status. Method: In total, 970 self‐administered questionnaires relating to health care usage were sent, via a clinical network of professionals and institutions, to children and adults with CP in Brittany, France. Frequency of use of different aspects of health care were analysed as a function of age and ambulatory status. Multivariate logistic regression evaluated differences in the frequency of each health care type with age; the transition from childhood to adulthood was specifically analysed. Results: The response rate was 53% (282 adults, 230 children). Use of medication (particularly psychotropic and analgesic) increased with age, while physical‐types of health care (rehabilitation, physical medicine and rehabilitation follow‐up, and equipment) decreased with age, independently of ambulatory status. Use of other treatments, such as botulinum toxin injections, was not influenced by age. The provision of rehabilitation was particularly affected by the period of transition. Interpretation: Although health care needs change naturally in adulthood, the large decrease in usage of specific types of rehabilitation after the transition to adulthood suggested individuals had difficulty accessing this type of health care after childhood. These results provide objectives for the development of patient‐centred, transitional consultations, and longitudinal studies. What this paper adds: Use of medication, particularly psychotropic and analgesic drugs, increased with age in individuals with cerebral palsy. Use of orthoses, physical medicine and rehabilitation physician follow‐up, and rehabilitation decreased with age. Transition from childhood to adulthood involved significant changes in health care usage. What this paper adds: Use of medication, particularly psychotropic and analgesic drugs, increased with age in individuals with cerebral palsy. Use of orthoses, physical medicine and rehabilitation physician follow‐up, and rehabilitation decreased with age. Transition from childhood to adulthood involved significant changes in health care usage. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.